External aggression to the limb as a predictive factor in the evolution of patients undergoing arterial revascularization (Clinics, 2005)
PURPOSE: A variety of predictive factors for the evolution of arterial grafts in patients with critical ischemia have been well defined in clinical studies, including diabetes mellitus, dialytic renal insufficiency, smoking, and distal arterial runoff. The goal of this study was to determine whether patients with critical ischemia undergoing arterial reconstruction in which ischemic lesions appeared spontaneously, compared to those in which the ischemic lesion appeared following an external aggression to the limb present different patterns of evolution. METHODS: From February 2002 to January 2004, 100 patients undergoing infra-inguinal arterial reconstruction were followed. They were divided into 2 groups: 1) the spontaneous group (n = 52), comprising individuals presenting with ischemic lesions of spontaneous origin and 2) the external aggression to the limb group (n = 48), comprising individuals for which an external causal mechanism for the appearance of the ischemic lesion was identified. The variables analyzed were limb salvage and graft functioning rates. RESULTS: Patients with spontaneous lesions had rates of limb salvage and graft functioning significantly lower than those for patients with lesions that were secondary to external aggression (42.3% versus 87.5%, respectively for both outcomes; P